Radiographic finding of sunray appearance as a sign of malignant mandibular lesion: a case report - Alfina, Risca; Rahman, Fadhlil Ulum Abdul; Yunus, Barunawaty; Ariestiana, Yossy Yoanita (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: To report the “sunray” appearance on panoramic radiography as a sign of malignancy lesions of the mandible. Case Report: A 40 year old female patient came to the Hasanuddin University Dental Hospital with the main complaint of facial swelling which causes an asymmetrical appearance and hard consistency on palpation. Mucosa around the second right premolar to the third right molar is reddish with an irregular border. The patient was referred to the radiology department for panoramic radiography and MRI. The panoramic radiograph revealed a mixed radiolucent-radiopaque lesion in tooth 35 involving ramus to the coronoid process. PDL space was irregular widening at 36, 37, and 38. The